Therapeutic effects of melittin on paclitaxel-induced peripheral neuropathic pain and spinal neuronal hyperactivity in male rats - Daxian Li; Daxian Li; Yan Wu; Yan Wu; Lirong Chang; Yizhi Song; Xiaoqiang Du; Fenqin Xue; Yang Liu; Yang Liu; Jie Wu; Jie Wu; et al. (Frontiers in Neuroscience)
IntroductionAs a taxane-based cytostatic agent, paclitaxel holds a broad spectrum of life-saving properties. However, its use is frequently limited by painful neuropathy in the extremities, which severely hinders the ultimate prognosis of cancer survivors. While bee venom therapy has shown promise in alleviating chemotherapy-induced neuropathic pain, the analgesic potential of its primary bioactive components, such as melittin and phospholipase A2 (bvPLA2), remains uncharacterized. This study investigated the ameliorative effects of melittin against paclitaxel-induced peripheral neuropathy in rats through integrated behavioral, in vivo electrophysiological, and neuropharmacological approaches.MethodsPaclitaxel was administered intraperitoneally (i.p.) at a total dose of 8 mg/kg. Cold and mechanical allodynia and hyperalgesia were quantified using the acetone drop and von Frey filament tests. To compare the therapeutic properties of bee venom ingredients, either melittin (0.5 mg/kg) or bvPLA2 (0.12 mg/kg) was administered subcutaneously at ST36 (Zusanli acupoint). In vivo extracellular recordings of wide dynamic range (WDR) neurons were performed in the spinal dorsal horn. Noradrenaline depletion was induced by the i.p. treatment with N-(2-Chloroethyl)-N-ethyl-2-bromobenzylamine (DSP-4, 50 mg/kg), and serotonin depletion was conducted by the i.p. administration of para-chlorophenylalanine (PCPA, 450 mg/kg).ResultsST36 treatment with melittin, but not bvPLA2, markedly impeded mechanical and cold hypersensitivity. Electrophysiological analysis revealed that paclitaxel induced spontaneous and stimulus-evoked hyperexcitation of spinal WDR neurons. Melittin selectively suppressed evoked neuronal activities (i.e., acute responses and after-discharges) without modulating the spontaneous firing of WDR neurons. Neuropharmacological investigation demonstrated that the effects of melittin were fully reversed by noradrenaline depletion, whereas serotonin depletion had no effect.DiscussionOur findings establish that melittin treatment at ST36 could ease paclitaxel-induced neuropathic pain by partially attenuating the hyperexcitable state of spinal WDR neurons. Furthermore, these ameliorative actions were mediated by the specific recruitment of the endogenous noradrenergic system. This study provides novel evidence supporting melittin as a targeted symptomatic agent for paclitaxel-induced peripheral neuropathy, which would advance the development of promising analgesic strategies in oncological care.